Find the best solutions to your questions at Westonci.ca, the premier Q&A platform with a community of knowledgeable experts. Get detailed answers to your questions from a community of experts dedicated to providing accurate information. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.

Using f(x) = 2x + 7 and g(x) = x-3, find f(g(-2)).

Sagot :

Answer:

f(g(-2)) = -3

Step-by-step explanation:

g(-2) = -2 - 3 = -5

f(-5) = 2(-5) + 7 = -10 + 7 = -3